2021
DOI: 10.1055/a-1334-8002
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles of the von Willebrand Factor Propeptide

Abstract: The primary polypeptide sequence of von Willebrand factor (VWF) includes an N-terminal 741-amino acid VWF propeptide (VWFpp). In cells expressing VWF, the VWFpp performs two critical functions. In the Golgi, VWFpp mediates the intermolecular disulfide linkages that generate high-molecular-weight VWF multimers. Subsequently, the VWFpp, which is proteolytically cleaved from mature VWF by furin, functions to generate the endothelial storage organelles (Weibel-Palade bodies) in which VWF and a distinct collection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…(affecting N-glycan attachment site) and p.Gly334Glu on the probabale functions of VWFpp in circulation remains to be understood (Rawley & Lillicrap, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(affecting N-glycan attachment site) and p.Gly334Glu on the probabale functions of VWFpp in circulation remains to be understood (Rawley & Lillicrap, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of our observations, we suggest these two variants should be considered benign variants rather than pathologic mutations. Nonetheless, due to the current suggested potential roles of VWFpp in hemostasis or associated physiological processes, such as angiogenesis and wound repair, the impact of the variants p.Asn211Asp (affecting N‐glycan attachment site) and p.Gly334Glu on the probabale functions of VWFpp in circulation remains to be understood (Rawley & Lillicrap, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, and/or alternatively, it has been suggested that there may also be an extracellular role for the VWF propeptide in hemostasis. 36 For individuals with variants in the VWF propeptide perhaps this function is also impaired or abolished and contributes to the increased bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The findings in the present study may point to some reasons for this increased bleeding potential including the absence of WPBs leading to the improper storage/release of other cargo proteins. Additionally, and/or alternatively, it has been suggested that there may also be an extracellular role for the VWF propeptide in hemostasis 36 . For individuals with variants in the VWF propeptide perhaps this function is also impaired or abolished and contributes to the increased bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, focused release of VWFpp from degranulating platelets during the initial thrombus formation and incorporation in the adhesive surface via laminin and collagen provides a mechanism to influence the adhesive properties of the exposed extracellular matrix and direct hemostatic and immune responses following vascular injury. Recent reports have emerged that VWFpp can support platelet adhesion to collagen surfaces and enhance thrombus mass in a glycan-dependent manner [50] and that in a murine model of deep vein thrombosis VWFpp incorporates in venous thrombi near regions of active thrombus formation [51].…”
Section: Discussionmentioning
confidence: 99%